The dictator's army battlefield effectiveness in authoritarian regimes - Talmadge, Caitlin (Cornell studies in security affairs, 2015)
A compelling new argument to help us understand why authoritarian militaries sometimes fight very well-and sometimes very poorly. Talmadge's framework for understanding battlefield effectiveness focuses on four key sets of military organizational practices